V28. KCNA2 mutations cause epileptic encephalopathy by gain- or loss-of channel function. Issue 8 (August 2015) - Hedrich, U.B.S.; Syrbe, S.; Riesch, E.; Djémié, T.; Müller, S.; Møller, R.S.; Maher, B.; Hernandez-Hernandez, L.; Synofzik, M.; Caglayan, H.S.; Arslan, M.; Serratosa, J.; et al.
<x xml:space="preserve">Abstract</x> Epileptic encephalopathies (EE) are a heterogeneous group of epilepsy syndromes associated with severe cognitive and behavioral disturbances. Amongst others, genes encoding neuronal ion channels have been identified as candidate genes for EE. Using next generation sequencing, we identified four different de novo mutations in KCNA2, encoding the voltage-gated potassium channel KV1.2. Voltage-gated potassium channels play an essential role in neuronal excitability, control the resting membrane potential and thresholds for action potential generation of a neuron and are responsible for repolarizing membranes back to resting values after action potential generation. Therefore, mutations in potassium channel-encoding genes have been shown to alter the neuronal excitability and cause different epilepsy syndromes, including EE. Here, we identified four independently occurring de novo KCNA2 mutations in six EE patients, with one mutation recurring three times. Four of the studied patients presented with febrile and multiple afebrile, often focal seizure types, multifocal epileptiform discharges strongly activated by sleep, mild-moderate ID, delayed speech development and sometimes ataxia. Functional studies were performed using an automated two-microelectrode voltage-clamp oocyte system. The two mutations associated with this phenotype revealed an almost complete loss-of-function with a dominant negative effect. Two further cases with KCNA2 mutations in the voltage sensor presented with an even more severe EE phenotype. These mutations caused a dramatic gain-of-function effect leading to permanent opening of KV1.2 channels. Therefore, KCNA2 is a novel gene involved in human neurodevelopmental disorders causing the clinical phenotype by two different mechanisms: (i) increasing the excitability or (ii) electrical silencing of KV1.2-expressing neurons.